Interview with Ken Schwartz, San Luis Obispo mayor, October 11, 1969 (1969)
Interview with San Luis Obispo mayor, Ken Schwartz, during half-time of a Cal Poly football game. [00:00:01] Interview with Mayor, Ken Swartz, begins [00:00:28] Interviewer asks the mayor his impressions on student involvement in the community [00:01:30] Interviewer asks mayor about projects that have had a large impact on the SLO community [00:01:40] Mayor talks about collections for feeding the needy, storm assistance, political clubs on campus, mission projects, and plenty of other projects [00:03:20] Interviewer asks if mayor thinks that the community needs a special type of attitude to realize the benefits of being a college community [00:03:40] Mayor talks about physical projects that have benefited the community, bridges, statues, creek cleanings. Lists more projects [00:05:15] Interviewer begins to wrap up interview